A β-Wrapin Targeting the N-Terminus of α-Synuclein Monomers Reduces Fibril-Induced Aggregation in Neurons - Szegő, Éva M.; Boß, Fabian; Komnig, Daniel; Gärtner, Charlott; Höfs, Lennart; Shaykhalishahi, Hamed; Wördehoff, Michael M.; Saridaki, Theodora; Schulz, Jörg B.; Hoyer, Wolfgang; Falkenburger, Björn H. (Frontiers in Neuroscience, 2021)
Reducing α-synuclein pathology constitutes a plausible strategy against Parkinson’s disease. As we recently demonstrated, the β-wrapin protein AS69 binds an N-terminal region in monomeric α-synuclein, interferes with fibril nucleation, and reduces α-synuclein aggregation in vitro and in a fruit fly model of α-synuclein toxicity. The aim of this study was to investigate whether AS69 also reduces α-synuclein pathology in mammalian neurons. To induce α-synuclein pathology, primary mouse neurons were exposed to pre-formed fibrils (PFF) of human α-synuclein. PFF were also injected into the striatum of A30P-α-synuclein transgenic mice. The extent of α-synuclein pathology was determined by phospho-α-synuclein staining and by Triton X-100 solubility. The degeneration of neuronal somata, dendrites and axon terminals were determined by immunohistochemistry. AS69 and PFF were taken up by primary neurons. AS69 did not alter PFF uptake, but AS69 did reduce PFF-induced α-synuclein pathology. PFF injection into mouse striatum led to α-synuclein pathology and dystrophic neurites. Co-injection of AS69 abrogated PFF-induced pathology. AS69 also reduced the PFF-induced degeneration of dopaminergic axon terminals in the striatum and the degeneration of dopaminergic dendrites in the substantia nigra pars reticulata. AS69 reduced the activation of astroglia but not microglia in response to PFF injection. AS69 reduced PFF-induced α-synuclein pathology and the associated neurodegeneration in primary neurons and in mouse brain. Our data therefore suggests that small proteins binding the N-terminus of α-synuclein monomers are promising strategies to modify disease progression in Parkinson's disease.